Electroluminescence transients and correlation with steady-state solar output in solution-prepared CH3NH3PbI3 perovskite solar cells using different contact materials - Córdoba, M. (2020)
Fil: Herrera Martínez, W.O. Comisión Nacional de Energía Atómica. Departamento de Energía Solar; Argentina